Tugas dan Tanggung Jawab Personil Sekolah dalam Kegiatan BK - Titi Sunarti; Anika Nuraeni; Alya Aprilia Aziza; Seli Kristiany; Rachel Alifa (Lembaga Pengembangan Kinerja Dosen, 2026)
Guidance and counseling is an essential service in the academic framework that aims to support the optimal development of students. The success of BK services does not only depend on the competence of guidance and counseling teachers, but also on the involvement and synergy of all school personnel. However, in practice, BK services are often understood as the individual responsibility of BK teachers, so that the roles of other school personnel have not been optimally integrated. This research seeks to delineate the duties and responsibilities of school personnel in guidance and counseling activities and to examine the patterns of collaboration that have been established in their implementation. This research utilizes a qualitative approach using a literature study method, with data sources in the form of accredited national journal articles and related scientific publications over the past five years. The data were evaluated by employing content analysis techniques to identify topics related to the roles of the principal, guidance counselors, homeroom teachers, subject teachers, and educational staff. Findings from this research indicate that the effectiveness of guidance and counseling services is greatly influenced by the clarity of the division of tasks, managerial support from the principal, and collaboration between school personnel. The findings also reveal a gap between the ideal concept of collaborative guidance and counseling services and their implementation in schools. The Scientific implications stress the vital role of strengthening coordination and integration of the roles of school personnel in developing more effective, systematic, and sustainable guidance and counseling services.